2010
DOI: 10.1007/s11270-009-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Prototype Pesticides Submitted to Conventional Water Treatment Conditions: The Influence of Major Parameters

Abstract: The behavior of several pesticides in aqueous solution, namely bifenthrin, amethrin (pyrethroid insecticides), endosulfan and endosulfan sulfate (organochlorine pesticides), disulfoton, methyl pyrimiphos, and phorate (organophosphorus pesticides), submitted to the conditions typically employed in water treatment stations was investigated. Continuous pesticide depletion was monitored by solid-phase microextraction sampling followed by gas chromatography-mass spectrometry analysis. The influence of major paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In LPME, the pH of the aqueous phase plays an important role on the extraction capabilities of compounds having ionizable groups. Most of the OPPs are degraded in strong acidic (pH < 3) and alkaline medium . The effect of pH on the extraction performance was therefore investigated in the range of 3.0–8.0.…”
Section: Resultsmentioning
confidence: 99%
“…In LPME, the pH of the aqueous phase plays an important role on the extraction capabilities of compounds having ionizable groups. Most of the OPPs are degraded in strong acidic (pH < 3) and alkaline medium . The effect of pH on the extraction performance was therefore investigated in the range of 3.0–8.0.…”
Section: Resultsmentioning
confidence: 99%
“…An increased implementation of Doehlert uniform shell designs in GC-MS has been observed in the last decade for developing efficient sample treatment methods by monitoring different analytical functions such as recovery [49][50][51][52][53][54][55], analytical signal [56][57][58][59][60][61] and reaction yield [51,62]. Table 4 also shows that regardless of the potential benefits of uniform shell designs, they have not gained widespread popularity among researchers for optimizing systematically and simultaneously GC-MS instrumental variables.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…The effect of several water treatment oxidation processes on the pesticides bifenthrin, amethrin, endosulfan, endosulfan sulfate, disulfoton, methyl pyrimiphos, and phorate was studied by Souza et al (2010). It was found that increased exposure times to UV irradiation led to increased degradation of the pesticides, with the organophosphate pesticide disulfoton needing less time than the organochlorine pesticide endosulfan sulfate to achieve complete degradation.…”
Section: Treatment Strategiesmentioning
confidence: 99%